New Peptide-Drug Conjugates for Precise Targeting of SORT1-Mediated Vasculogenic Mimicry in the Tumor Microenvironment of TNBC-Derived MDA-MB-231 Breast and Ovarian ES-2 Clear Cell Carcinoma Cells - Charfi, Cyndia; Demeule, Michel; Currie, Jean-Christophe; Larocque, Alain; Zgheib, Alain; Danalache, Bogdan Alexandru; Ouanouki, Amira; Béliveau, Richard; Marsolais, Christian; Annabi, Borhane (Frontiers in Oncology, 2021)
Vasculogenic mimicry (VM) is defined as the formation of microvascular channels by genetically deregulated cancer cells and is often associated with high tumor grade and cancer therapy resistance. This microcirculation system, independent of endothelial cells, provides oxygen and nutrients to tumors, and contributes also in part to metastasis. VM has been observed in ovarian cancer and in triple negative breast cancer (TNBC) and shown to correlate with decreased overall cancer patient survival. Thus, strategies designed to inhibit VM may improve cancer patient treatments. In this study, sortilin (SORT1) receptor was detected in in vitro 3D capillary-like structures formed by ES-2 ovarian cancer and MDA-MB-231 TNBC-derived cells when grown on Matrigel. SORT1 gene silencing or antibodies directed against its extracellular domain inhibited capillary-like structure formation. In vitro, VM also correlated with increased gene expression of matrix metalloproteinase-9 (MMP-9) and of the cancer stem cell marker CD133. In vivo ES-2 xenograft model showed PAS+/CD31- VM structures (staining positive for both SORT1 and CD133). TH1904, a Doxorubicin-peptide conjugate that is internalized by SORT1, significantly decreased in vitro VM at low nM concentrations. In contrast, VM was unaffected by unconjugated Doxorubicin or Doxil (liposomal Doxorubicin) up to uM concentrations. TH1902, a Docetaxel-peptide conjugate, altered even more efficiently in vitro VM at pM concentrations. Overall, current data evidence for the first time that 1) SORT1 itself exerts a crucial role in both ES-2 and MDA-MB-231 VM, and that 2) VM in these cancer cell models can be efficiently inhibited by the peptide-drug conjugates TH1902/TH1904. These new findings also indicate that both peptide-drug conjugates, in addition to their reported cytotoxicity, demonstrate a bystander effect by inhibiting VM in SORT1-positive TNBC and ovarian cancers.